Waiting list management practices for home‐care occupational therapy in the province of Quebec, Canada. (11th February 2015) - Raymond, Marie‐Hélène; Demers, Louise; Feldman, Debbie E.
Abstract: Referral prioritisation is commonly used in home‐based occupational therapy to minimise the negative impacts of waiting, but this practice is not standardised. This may lead to inequities in access to care, especially for clients considered as low priority, who tend to bear the brunt of lengthy waiting lists. This cross‐sectional study aimed to describe waiting list management practices targeting low‐priority clients in home‐based occupational therapy in the province of Quebec, Canada, and to investigate the association between these practices and the length of the waiting list. A structured telephone interview was conducted in 2012–2013 with the person who manages the occupational therapy waiting list in 55 home care programmes across Quebec. Questions pertained to strategies aimed at servicing low‐priority clients, the date of the oldest referral and the number of clients waiting. Results were analysed using descriptive statistics and non‐parametric tests. The median wait time for the oldest referral was 18 months (range: 2–108 months). A variety of strategies were used to service low‐priority clients. Programmes that used no strategies to service low‐priority clients ( n  = 16) had longer wait times ( P  < 0.0001) and a greater number of people on the waiting list ( P  = 0.006) compared with programmes that applied a maximum wait time target ( n  = 12). In conclusion, diverse strategies exist to allocate services to low‐priority clients in home‐based occupational therapy programmes. However, in programmes where none of these strategies are used, low‐priority clients may be denied access to services indefinitely.